If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 3 = 50c + -6 Reorder the terms: 3 + 2c = 50c + -6 Reorder the terms: 3 + 2c = -6 + 50c Solving 3 + 2c = -6 + 50c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-50c' to each side of the equation. 3 + 2c + -50c = -6 + 50c + -50c Combine like terms: 2c + -50c = -48c 3 + -48c = -6 + 50c + -50c Combine like terms: 50c + -50c = 0 3 + -48c = -6 + 0 3 + -48c = -6 Add '-3' to each side of the equation. 3 + -3 + -48c = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -48c = -6 + -3 -48c = -6 + -3 Combine like terms: -6 + -3 = -9 -48c = -9 Divide each side by '-48'. c = 0.1875 Simplifying c = 0.1875
| 6-5c=-4c | | -2a+3=9 | | 3(0)-9(3)=15 | | 2n-5=4n-7 | | 48=4n-4 | | 8a+18=6a+30 | | 4x^2+378x-4248.5=0 | | 8k=1 | | z/3=19=25 | | 10z-6=14 | | sin(3x)+cos(6x)=1 | | 8a-18=6a+30 | | 3v-5=8 | | k/2-1=1 | | (11x)+(6x+5)=180 | | 2=3d-4 | | 4z-7=9 | | 5a-6=56 | | f(x)=2x^2+6x-1 | | 20=x+x*0.2 | | 6x=(8-0.25x)-(6-0.75) | | 7x+11=3*4+2 | | 100+20a=220 | | 5a+6= | | 2x+7*3=22*3+x | | 9(y+1)(y+1)-9=0 | | 4(y-1)(y-1)-9=0 | | .4*x+.6*8=9.5 | | 11g+3=12g | | -17-2a=1 | | -4+17(x)=183 | | -5x+y=-7 |